2019
DOI: 10.22146/jh.44206
|View full text |Cite
|
Sign up to set email alerts
|

Crime Prevention Through Community Policing Interventions: Evidence from Harar City, Eastern Ethiopia

Abstract: In Ethiopia, community policing has been announced ofcially as a national program in 2005 E.C with the impetus to nullify crimes at lower tiers. There have been growing reports of prevailing crimes in Jenila district of Harar city. Accordingly, this study endeavors to scrutinize the practices of community policing and associated challenges in the study site. A mixed research deign was used to fetch out primary and secondary data sets. Hence, the participants’ views were captured through questionnaires, key inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…(Zikhali, 2019) Perpolisian Masyarakat di Ethiopia bisa menumbuhkembangkan keasadaran masyarakat dalam menanggunglangi kejahatan, sehingga masyarakat berpandangan bahwa keamanan masyarakat merupakan kebutuhan bersama. (Italemahu, 2019) Ini menunjukkan pentingnya kemitraan polisi dan masyarakat untuk menanggulangi kejahatan, tanpa strategi ini tidak akan efektif dalam menanggulangi gangguan kamtibmas /kejahatan.…”
Section: Pendahuluanunclassified
“…(Zikhali, 2019) Perpolisian Masyarakat di Ethiopia bisa menumbuhkembangkan keasadaran masyarakat dalam menanggunglangi kejahatan, sehingga masyarakat berpandangan bahwa keamanan masyarakat merupakan kebutuhan bersama. (Italemahu, 2019) Ini menunjukkan pentingnya kemitraan polisi dan masyarakat untuk menanggulangi kejahatan, tanpa strategi ini tidak akan efektif dalam menanggulangi gangguan kamtibmas /kejahatan.…”
Section: Pendahuluanunclassified
“…The practice of community policing in Kenya seeks to expand the partnership to all other government agencies, the private sector, Non-Government Organizations (NGO's), and Civil Society Organisations (CSO's). The overall goal is to improve public safety and the quality of life for all persons and it falls on the premise that police alone cannot control crime and disorder and promote residents' quality of life [1]. Studies have also shown that when the public cooperates with the police by reporting crime, identifying suspects, and mitigating the social conditions that lead to crime, the police become more effective in their public safety role.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Durban, Kalina et al (2019) highlighted the phenomenon of securitization as a tool for the on-going privatization of public space, which is done at the expense of excluding urban poor citizens. This worldwide phenomenon is not only peculiar to South Africa (Frühling and Cancina, 2005;Lemanski, 2006;Maguire et al, 2017;Rukus et al, 2018;Adugna and Italemahu, 2019;Karreth, 2019;Thuku, 2021). Indeed, urban space is a contested space, and if one adds the right to the city discourse, crime, safety, security, and, at times, violence are used as the instruments in (re)producing and (co)production of spatial enclaves of crime, safety, and security.…”
Section: Introductionmentioning
confidence: 99%